2010
DOI: 10.1007/s00726-010-0598-z
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of l-arginine on reducing obesity: potential mechanisms and important implications for human health

Abstract: Over the past 20 years, growing interest in the biochemistry, nutrition, and pharmacology of L-arginine has led to extensive studies to explore its nutritional and therapeutic roles in treating and preventing human metabolic disorders. Emerging evidence shows that dietary L-arginine supplementation reduces adiposity in genetically obese rats, diet-induced obese rats, finishing pigs, and obese human subjects with Type-2 diabetes mellitus. The mechanisms responsible for the beneficial effects of L-arginine are l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
164
3
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 238 publications
(177 citation statements)
references
References 65 publications
8
164
3
2
Order By: Relevance
“…L-Arginine also increased b-cell neogenesis and antioxidant defenses in rats treated with alloxan and aided recovery of endothelium-dependent relaxation in patients with type 2 diabetes (Pieper & Dondlinger 1997, Vasilijevic et al 2007). Administration of L-arginine has also been reported to reduce adiposity in obese-diabetic humans, genetic and diet-induced obese rats as well as finishing pigs (McKnight et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…L-Arginine also increased b-cell neogenesis and antioxidant defenses in rats treated with alloxan and aided recovery of endothelium-dependent relaxation in patients with type 2 diabetes (Pieper & Dondlinger 1997, Vasilijevic et al 2007). Administration of L-arginine has also been reported to reduce adiposity in obese-diabetic humans, genetic and diet-induced obese rats as well as finishing pigs (McKnight et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, unlike our findings, they did not see any affect on the levels of triglycerides and total cholesterol. These differing results may be due to the short duration of their study, as well as the high BMI and average age of their participants (46 ± 5) 36 .…”
Section: Discussionmentioning
confidence: 88%
“…In a study conducted in 2008 by Boger et al, supplementation with L-arginine improved the function of the cardiovascular system in patients on hemodialysis 31 . Several studies that were carried out on humans and male C57BL/6 mice have shown that L-arginine supplementation may be considered a new treatment for metabolic disorders and also has an effect of lowering blood pressure, adipose tissue and weight and improves insulin sensitivity [32][33][34] . In a study conducted by Martina et al L-arginine supplementation of 2.1 g per day in combination with N-acetylcysteine at a dose of 2.1 g per day for 6 months has been shown to improve endothelial function 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Arginine exerts an anti-obesity effect, reduces fat content, and inhibits the growth of white adipose tissue [30]. The anti-obesity effect of HFD-FMIX may be attributed to amino acids such as arginine.…”
Section: Discussionmentioning
confidence: 99%